Modelo de participación comunitaria en el sistema educativo de nivel básico en el cantón San Miguel de Urcuquí - Mogrovejo Rogríguez, María José (2005)
To this end a participatory assessment with key stakeholders, whose views allowed us to establish the critical points based on which we design a model of decentralization of education in the Canton San Miguel de Urcuquí was performed. The implementation of the proposal ultimately depends on the Municipal Government in accordance with the Constitution of the Republic and the Municipal Government Act has the authority to do so.